Does FDI Bring Good Jobs to Host Countries? - Javorcik, Beata (World Bank, Washington, DC, 2013)
This study examines whether jobs created as a result of foreign direct investment (FDI) inflows can be considered to be good jobs both from the worker’s and the country’s perspective. For the worker, such jobs are likely to pay higher wages than jobs in indigenous firms in developing countries, and foreign employers tend to offer more training than local firms. From the country’s perspective, jobs in foreign affiliates are good, because FDI inflows tend to increase the aggregate productivity of the host country. Existence of positive externalities associated with FDI may suggest that government intervention in the form of subsidies aimed at increasing FDI inflows may be warranted, but investment promotion activities may offer a less costly course of action, because obtaining information on investment opportunities in developing countries tends to be more difficult than gathering data in industrialized economies. Once FDI enters the country, governments may wish to maximize the productivity benefits by assisting local firms with becoming suppliers to foreign affiliates by extending subsidized credit to prospective suppliers of foreign affiliates or by setting up supplier development programs to bring local firms and foreign affiliates together.